Geriatric assessment predicts survival and toxicities in elderly myeloma patients: an International Myeloma Working Group report - Palumbo, Antonio; Bringhen, Sara; Mateos, Maria-Victoria; Larocca, Alessandra; Facon, Thierry; Kumar, Shaji K; Offidani, Massimo; McCarthy, Philip; Evangelista, Andrea; Lonial, Sagar; Zweegman, Sonja; Musto, Pellegrino; et al. (Blood, 2015)
We conducted a pooled analysis of 869 individual newly diagnosed elderly patient data from 3 prospective trials. At diagnosis, a geriatric assessment had been performed. An additive scoring system (range 0-5), based on age, comorbidities, and cognitive and physical conditions, was developed to identify 3 groups: fit (score = 0, 39%), intermediate fitness (score = 1, 31%), and frail (score ≥2, 30%). The 3-year overall survival was 84% in fit, 76% in intermediate-fitness (hazard ratio [HR], 1.61; P = .042), and 57% in frail (HR, 3.57; P < .001) patients. The cumulative incidence of grade ≥3 nonhematologic adverse events at 12 months was 22.2% in fit, 26.4% in intermediate-fitness (HR, 1.23; P = .217), and 34.0% in frail (HR, 1.74; P < .001) patients. The cumulative incidence of treatment discontinuation at 12 months was 16.5% in fit, 20.8% in intermediate-fitness (HR, 1.41; P = .052), and 31.2% in frail (HR, 2.21; P < .001) patients. Our frailty score predicts mortality and the risk of toxicity in elderly myeloma patients. The International Myeloma Working group proposes this score for the measurement of frailty in designing future clinical trials. These trials are registered at www.clinicaltrials.gov as #NCT01093136 (EMN01), #NCT01190787 (26866138MMY2069), and #NCT01346787 (IST-CAR-506).